1992
DOI: 10.1111/j.1365-2958.1992.tb01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribosomal association of the yeast SAL4 (SUP45) gene product: implications for its role in translation fidelity and termination

Abstract: The SAL4 gene of the yeast Saccharomyces cerevisiae encodes a novel translation factor (Sal4p) involved in maintaining translational fidelity. Using a polyclonal antibody raised against a Sal4p-beta-galactosidase fusion protein, Sal4p was shown to be almost exclusively associated with the ribosomal fraction. Even when the ribosomes were treated with 0.8 M KCl, only low levels of Sal4p were detected in the post-ribosomal supernatant, suggesting a very strong affinity between Sal4p and the ribosome. Analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
1

Year Published

1995
1995
2000
2000

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 39 publications
1
48
1
Order By: Relevance
“…Two explanations are offered; the first is that such eRF1 mutants might be strong suppressors that may not support yeast viability and so were not isolated+ A second explanation is that stop codon FIGURE 6. Western blot analysis of ribosome-bound eRF1 and eRF3 in the eRF1 mutant strains+ Ribosomal fractions were prepared from the sup45-disruptant strain IS37/7b supported by either the wild-type SUP45 ϩ allele, or each of the mutant alleles+ Proteins (25 mg) were separated using SDS-PAGE, and either stained with Coomassie Blue to verify equivalent loadings (A), or blotted onto nitrocellulose and probed with anti-eRF3 antibody (B), or anti-eRF1 antibody (C)+ Antibody binding was visualized using secondary antibody and chemiluminescent detection (see Materials and methods)+ The migration positions of molecular mass standards are marked, as are western blot bands corresponding to eRF1 (49 kDa) and eRF3 (79 kDa)+ The second, heavier (70 kDa) band on the eRF1 western blot is routinely seen using this affinity purified antibody preparation (Stansfield et al+, 1992)+ Western blot samples are split between blot 1 and blot 2, each with its own SUP45 ϩ control+ recognition by eRF1 might be "holistic"; in other words, a subtle interplay between eRF1 amino acids comprising a stop codon binding site achieves cooperative codon recognition, and a mutation affecting recognition of one stop codon inevitably has consequences for recognition of the other two+ All the mutants exhibit increased UAA suppression to varying degrees+ However, we believe our estimates of the true abilities of the mutant eRF1s to recognize UAA were distorted by the presence of the SUQ5 suppressor tRNA present in the IS37/7b strain background; SUQ5, unlike the cell's population of natural suppressor tRNAs, is cognate for UAA, and miscognate for UAG, and so will artificially increase suppression of UAA, and to a lesser extent UAG, above that which would be detected in a wild-type tRNA background+ In addition to stop-codon-suppression biased eRF1 alleles, the screens also identified the omnipotent suppressors sup45-702, sup45-718, and sup45-731, although these mutants phenotypically suppressed only the ade1-14 mutation+ Presumably these mutants suppressed lys2-864 UAG and his7-1 UAA stop codons weakly+ Curiously, mutants 702, 718, and 731 also show very low levels of UGA suppression (measured with the lacZ reporter system) despite being isolated as ade1-14 suppressors+ This is not because the ade1-14 premature stop codon is in an easily-suppressed nucleotide context, although context does have important effects on stop recognition by eRF1 in yeast (Bonetti et al+, 1995;Mottaguitabar et al+, 1998)+ Sequence analysis of the premature ade1-14 UGA stop codon identified the mutated codon as TGG (Trp 244) r TGA in the context TTC TGA AAC (data not shown), which defines a reasonably good eRF1 substrate (Bonetti et al+, 1995;Mottaguitabar et al+, 1998)+…”
Section: Screening For Erf1 Unipotent Suppressorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Two explanations are offered; the first is that such eRF1 mutants might be strong suppressors that may not support yeast viability and so were not isolated+ A second explanation is that stop codon FIGURE 6. Western blot analysis of ribosome-bound eRF1 and eRF3 in the eRF1 mutant strains+ Ribosomal fractions were prepared from the sup45-disruptant strain IS37/7b supported by either the wild-type SUP45 ϩ allele, or each of the mutant alleles+ Proteins (25 mg) were separated using SDS-PAGE, and either stained with Coomassie Blue to verify equivalent loadings (A), or blotted onto nitrocellulose and probed with anti-eRF3 antibody (B), or anti-eRF1 antibody (C)+ Antibody binding was visualized using secondary antibody and chemiluminescent detection (see Materials and methods)+ The migration positions of molecular mass standards are marked, as are western blot bands corresponding to eRF1 (49 kDa) and eRF3 (79 kDa)+ The second, heavier (70 kDa) band on the eRF1 western blot is routinely seen using this affinity purified antibody preparation (Stansfield et al+, 1992)+ Western blot samples are split between blot 1 and blot 2, each with its own SUP45 ϩ control+ recognition by eRF1 might be "holistic"; in other words, a subtle interplay between eRF1 amino acids comprising a stop codon binding site achieves cooperative codon recognition, and a mutation affecting recognition of one stop codon inevitably has consequences for recognition of the other two+ All the mutants exhibit increased UAA suppression to varying degrees+ However, we believe our estimates of the true abilities of the mutant eRF1s to recognize UAA were distorted by the presence of the SUQ5 suppressor tRNA present in the IS37/7b strain background; SUQ5, unlike the cell's population of natural suppressor tRNAs, is cognate for UAA, and miscognate for UAG, and so will artificially increase suppression of UAA, and to a lesser extent UAG, above that which would be detected in a wild-type tRNA background+ In addition to stop-codon-suppression biased eRF1 alleles, the screens also identified the omnipotent suppressors sup45-702, sup45-718, and sup45-731, although these mutants phenotypically suppressed only the ade1-14 mutation+ Presumably these mutants suppressed lys2-864 UAG and his7-1 UAA stop codons weakly+ Curiously, mutants 702, 718, and 731 also show very low levels of UGA suppression (measured with the lacZ reporter system) despite being isolated as ade1-14 suppressors+ This is not because the ade1-14 premature stop codon is in an easily-suppressed nucleotide context, although context does have important effects on stop recognition by eRF1 in yeast (Bonetti et al+, 1995;Mottaguitabar et al+, 1998)+ Sequence analysis of the premature ade1-14 UGA stop codon identified the mutated codon as TGG (Trp 244) r TGA in the context TTC TGA AAC (data not shown), which defines a reasonably good eRF1 substrate (Bonetti et al+, 1995;Mottaguitabar et al+, 1998)+…”
Section: Screening For Erf1 Unipotent Suppressorsmentioning
confidence: 99%
“…DNA manipulation and plasmid construction was carried out according to standard protocols (Sambrook et al+, 1989)+ To generate plasmid pGB1, a 2+64-kb Sal I/XhoI fragment from plasmid pUKC638 (a gift from K+M+ Jones and M+F+ Tuite, University of Kent) containing the entire SUP45 gene and its promoter was cloned into the XhoI site of pRS315 (Sikorski & Hieter, 1989)+ Plasmid pUKC802 (SUP45-URA3 ) is described elsewhere (Stansfield et al+, 1992)+ To generate plasmid pGB4, plasmid pUKC600, containing the entire SUP45 gene including its promoter on a Sal I/XhoI fragment in pBluescript (Stratagene), was first cut with HindIII/XbaI+ The resulting DNA was treated with Klenow enzyme and religated to generate plasmid pGB2+ A 3+8-kb BamHI/Bgl II fragment from pNKY51 (American Type Culture Collection; Alani et al+, 1987) containing the hisG-URA3-hisG "ura-blaster cassette" was subcloned into the SUP45 coding region in plasmid pGB2 cut with BamHI and Bgl II, generating plasmid pGB4+…”
Section: Plasmid Constructsmentioning
confidence: 99%
See 1 more Smart Citation
“…These phenotypes are consistent with the mutants having a defect in translation termination since the efficiency of nonsense suppression reflects the ability of a suppressor tRNA to compete with the endogenous termination mechanism for a stop codon (in the case of the SUQ5 suppressor, UAA) positioned at the ribosomal A site. A defect in the termination mechanism will be expected to increase the efficiency with which the suppressor tRNA is able to recognise the cognate codon.The product of the SUP45 gene (originally designated Sup45p) is a 438-amino-acid polypeptide (Breining and Piepersberg, 1986), which is tightly associated with the ribosome and is present in exponentially growing cells at a stoichiometry of approximately 1 mol Sup45p/20 mol ribosomes (Stansfield et al, 1992 with an AUG codon followed by a tetranucleotide stop signal: Sup45p-dependent peptidyl-releaqe activity stimulates release of 35S-labelled methionine from methionyl-tRNA on the ribosome (Frolova et al, 1994). This in vitm release-factor activity is greatly stimulated by a Xenopus laevis homologue of the SUP35 gene, an observation that led these workers to designate the two proteins eRFl (Sup45p) and eRF3 (Sup35p; Zhouravleva et al, 1995) by analogy with the protein release factors (RF-1, RF-2 and RF-3) known to mediate translation termination in prokaryotes (Craigen et al, 1990).…”
mentioning
confidence: 99%
“…The product of the SUP45 gene (originally designated Sup45p) is a 438-amino-acid polypeptide (Breining and Piepersberg, 1986), which is tightly associated with the ribosome and is present in exponentially growing cells at a stoichiometry of approximately 1 mol Sup45p/20 mol ribosomes (Stansfield et al, 1992). A mammalian homologue of Sup45p (showing 68% amino acid identity to the yeast protein; Frolova et al, 1994) demonstrates a low level of release-factor activity in an in vitro system that utilises rabbit ribosomes programmed with an AUG codon followed by a tetranucleotide stop signal: Sup45p-dependent peptidyl-releaqe activity stimulates release of 35S-labelled methionine from methionyl-tRNA on the ribosome (Frolova et al, 1994).…”
mentioning
confidence: 99%